ARTEMIY KHALATOV, THE RECTOR OF THE MOSCOW INSTITUTE OF NATIONAL ECONOMY. PAGES OF HISTORY OF THE PLEKHANOV RUSSIAN UNIVERSITY OF ECONOMICS - Irina M. Kornilova (Plekhanov Russian University of Economics, 2017)
The article describes the development of the Moscow Institute of National Economy (MINKH) connected with academic and public activity of A.B. Khalatov, the Rector of MINKH during one of the most complicated and controversial periods of soviet history. It raises the issue of thorough analysis of the faculty activity and first of all the Institute leaders, whose activity was kept concealed for a long time due to certain political circumstances. The authors discuss the necessity of further highlighting the contribution of academics of the Russian Plekhanov University of Economics to establishment and development of the Russian state system, public, political and cultural life of the country at different stages of its history.